Microsoft Exchange server 2003 administration - Chambers, Larry (Thomson /Course Technology, 2006)
This hands-on guidebook is designed to prepare students for the MCSE certification exam and for the challenges they will face as Microsoft networking professionals. Projects and exercises reinforce skills as they are learned and extensive test preparation resources help students get ready for exam day